Quality of care in long-term care institutions: A scoping review of literature (Research, Society and Development, 2021)
This review sought to answer the question “What theoretical models have been used to define and evaluate the quality of care provided to older adults in long-term care institutions?” The employed study methodology followed the recommendations of the Joanna Briggs Institute Reviewers Manual. Using MESH terms and keywords such as “elderly,” “long-term care,” and “theoretical,” four electronic databases (i.e., PubMed, Scopus, Web of Science, and LILACS) were searched for articles in Portuguese, English, and Spanish, without a time frame restriction. Titles and abstracts were independently screened by two reviewers, followed by a full-text review. A total of 1,211 articles met our inclusion criteria, 80 were selected for full reading, and 21 were included for qualitative synthesis. The theoretical models cited in the studies included the multidimensional model (n = 10); the structure, process, and results model (n = 8); a theory centered on the person (n = 2); and one centered on the work environment (n = 1). Few articles used a conceptual model as the basis for assessing long-term care institutions, which is important for the construction of instruments and indicators that assess the quality of care.